2016
DOI: 10.1007/s00467-015-3309-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of serum cystatin C for estimating the glomerular filtration rate in preterm infants

Abstract: Reference ranges for Cys-C in premature infants decline gradually over the first year after birth. Cys-C appears to be a more reliable marker than Cre for estimating GFR in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Recent research suggests that CysC levels are independent of birth weight and gestational age. 3,18,24,25 In this study, with larger samples, we confirmed that CysC is independent of BW and GA in newborns, at least within 3 days after birth (p > 0.05).…”
Section: Discussionsupporting
confidence: 71%
“…Recent research suggests that CysC levels are independent of birth weight and gestational age. 3,18,24,25 In this study, with larger samples, we confirmed that CysC is independent of BW and GA in newborns, at least within 3 days after birth (p > 0.05).…”
Section: Discussionsupporting
confidence: 71%
“…The available literatures have shown that CysC is independent of birth weight and gestational age [3,24,25,19]. In this study, with larger samples, we further confirmed CysC is independent of BW and GA in newborn, at least within 3 days after birth (P>0.01).…”
Section: (Show In Table 2)supporting
confidence: 83%
“…18 As for preterm infants, the Cys-C level varied widely in previous reports. 22,23 With regards to this issue Kandasamy et al once summarised a related systematic review, and found the Cys-C level of neonates fluctuates between 1.00 and 2.52 mg/L in different researches. 24 In our opinion, the inconsistent data was mainly caused by different grouping methods, different sample sizes, the interference of diseases and so on.…”
Section: Discussionmentioning
confidence: 99%